Studies on carbon dioxide capture using polymer based carbon adsorbents - Tiwari, Deepak (My University, 2018)
Carbon dioxide (CO2), a major greenhouse gas, is one of the greatest challenges of the twenty-first century. Its increase in the atmosphere is mainly due to fossil-fuel power sector and energy-intensive industries. Consequences like global warming and climate change concerns initiated global efforts to reduce CO2 concentration. Among the various mitigation pathways, CO2 capture and storage (CCS) technology is attracting higher interest which can lower down the release of CO2 into the atmosphere. Pre-combustion, post-combustion, and oxy-fuel combustion are the CCS technologies among which post combustion is considered as economic and green technologies. The available post-combustion technologies for CO2 capture are absorption, adsorption, cryogenic distillation, and membrane separation. Mature technology like absorption has been used most but it is having disadvantages like high regeneration cost, equipment corrosion, and amine oxidative degradation. Adsorption is believed to be economically and least interfering ways due to its easy application as it fulfills the objective of very small modification to power plants, less energy penalty and low equipment cost. Therefore, for post-combustion CO2 capture, there is a great need for the development of adsorbent materials with high adsorption capacity, selectivity and fast kinetics coupled with good thermal and mechanical stability. Carbon based adsorbents are found to be attractive and have been extensively used for CO2 adsorption due to its high surface area, lesser amount of energy for regeneration, good thermal/mechanical stability and hydrophobicity. It was seen that many researchers were trying to develop adsorbent either by direct carbonization or by physical/chemical activation. Also, they tried to evaluate their uptake capacity mainly under static condition at room temperature. But, the disadvantage of their studies is both the synthesis and performance evaluation. It was reported that direct carbonized adsorbent synthesis was time consuming and requires high amount of energy. Moreover, CO2 adsorption under static condition provides higher value but it is not applicable for flue gas applications. Thus, objectives of our work are to overcome this gap, in which nanocasting technique, direct carbonization followed by activation using appropriate activation conditions and carbon sources having higher nitrogen and oxygen contents is carried out to improve the texture, surface properties and CO2/N2 selectivity of carbon adsorbents. Also, adsorption study under dynamic fixed bed conditions at different CO2concentrations (5-12.5%) and temperatures (30-100 °C), which is more important than static conditions, adsorption kinetics, binary system adsorption equilibria and thermodynamics have been carried. Three different types of nanostructured carbons were developed by nanocasting technique for capture of CO2 under simulated flue gas conditions. Three polymeric materials namely melamine-formaldehyde, urea-formaldehyde and epoxy resins were synthesized and were used as polymeric precursors for nanocasting technique along with mesoporous zeolite as hard template. Also, using direct carbonization followed by a standard chemical activation with KOH at appropriate activation conditions were used. Developed adsorbents were characterized using various sophisticated techniques namely N2 sorption isotherms, XRD (X-ray diffraction), TEM (transmission electron microscopy), SEM (scanning electron microscopy), TGA (thermogravimetric analysis), CHNS (elemental analysis), FTIR (Fourier transform infrared spectroscopy), TPD (temperature programmed desorption), XPS (X-ray photoelectron spectroscopy), and Raman spectroscopy. Dynamic adsorption-desorption experiments were conducted in the fixed-bed system to evaluate their CO2 adsorption capacities, selectivity and regenerability under simulated flue gas conditions. CO2 adsorption was studied at several adsorption temperatures (30 to 100 °C) under varying CO2 concentrations (5% to 12.5% by volume). Three kinetic models i.e., pseudo-first order, pseudo second order and fractional order kinetic models were used to fit CO2 adsorption kinetics on the prepared adsorbents. The equilibrium adsorption data fitted with three isotherm model i.e., Langmuir, Freundlich and Temkin isothermal models Thermodynamic functions such as molar Gibbs free energy change, entropy change, and enthalpy change were evaluated numerically. Finally, energy duty for desorption of adsorbed CO2 and energy penalty for the whole process system was also estimated.Nitrogen enriched carbon adsorbents were successfully prepared using precursor melamine-formaldehyde resin and mesoporous zeolite (MCM-41) as template through nanocasting technique. Different characterization techniques were used for the thorough characterization of the prepared adsorbents. Using physical activation with CO2 and high nitrogen content carbon precursor resulted in a development of nanostructured carbon denoted as MFZ-700. This sample possesses a surface area of 193 m2 g -1 , pore volume of 0.32 cm3 g-1 and nitrogen content of 22.27%. Dynamic CO2 uptake capacity of 0.64 mmol g-1 for the sample (MFZ-700) at 30 °C under 12.5% CO2 flow was obtained. Complete regenerability for the adsorbents over four adsorption-desorption cycles was obtained. Furthermore, fractional order kinetic models provided best description over all adsorption temperatures and CO2 concentrations. Heterogeneity of the adsorbent surface was confirmed from Temkin isotherms fit and isosteric heat of adsorption values. The isosteric heat of adsorption is found to be 15.05 kJ mol-1 , which indicates physiosorption process and also supports easy regenerability of the adsorbent. Thermodynamic parameters ∆𝐻 0 and ∆𝑆 0 are estimated to be -5.7 kJ mol-1 and 0.033 kJ mol-1 K -1 . The energy penalty estimated for the whole process is 2.15 MJ per kg CO2. Oxygen enriched carbon adsorbents were successfully synthesized for the first time from template zeolite and epoxy resin as precursor using a nanocasting technique. Carbonization and CO2 activation were performed at various temperatures (500 to 800 °C) to prepare different carbon structure adsorbents. Several characterization techniques were used to characterize for the textural properties, oxygen content and surface functional groups of the adsorbents. The carbon adsorbents show high oxygen content (53.98 %), highest surface area (SBET = 686 m2 g -1 ) and pore volume (0.60 cm3 g -1 ). The materials were evaluated using fixedbed adsorption and the highest CO2 uptake of 0.65 mmol g-1 was observed due to highly basic nature of the surface. Regeneration studies of adsorbent indicated easy regenerability and stable operation over four adsorptions-desorption cycles. Kinetic models for CO2 adsorption at various CO2 concentrations and temperatures were studied. The fractional order provided best fitting for the adsorption behavior with an error of less than 5%. The experimental data for CO2 adsorption were analyzed using different isotherm models and found that the Freundlich isotherm model presented perfect fit among all isotherm models considered indicating adsorbent surface to be heterogeneous. The isosteric heat of adsorption is 9.09 kJ mol-1 , indicating physiosorption process. The values of ∆𝐺 0 and ∆𝐻 0 have confirmed the adsorption process to be spontaneous and exothermic in nature. Urea-formaldehyde resin (high nitrogen) as precursor and mesoporous zeolite (MCM41) as template, using nanocasting technique results in development of nanostructured cabon having high surface area (337 m2 g-1), mesopores (0.644 cm3 g-1 ), and micropores (0.123 cm3 g-1). The CO2 capture capacity depends more on the nitrogen functionalities in addition to textural properties and nitrogen content as UFZ-700 shows highest CO2 uptake of 0.84 mmol g-1. Furthermore, it was found that adsorbent can be easily regenerated, which was also seen by the lower value of isosteric heat of adsorption. Four adsorption-desorption cycles showestablished materials’ excellent stability as an adsorbent. Different kinetic models were fitted for the adsorption data and on the basis of correlation coefficient (R2), fractional order provided best fit with the experimental data. Heterogeneous adsorbent surface was confirmed from best fit of equilibrium adsorption data with Freundlich isotherm. Exothermic, feasible and spontaneous nature was confirmed from thermodynamic values. High surface area nitrogen enriched carbon adsorbents were prepared from a low cost and widely available urea-formaldehyde resin using a standard chemical activation with KOH. Maximum surface area and total pore volume of 4547 m2 g-1 and 4.50 cm3 g-1 respectively were found by controlling the activation conditions. Nitrogen content of this sample was 5.62%. Maximum CO2 uptake of 1.40 mmol g-1for UFA-3-700 at 30 °C under 12.5% CO2 flow was obtained. Complete regenerability of the adsorbents over multiple adsorption-desorption cycles was obtained. Fractional order kinetic model provided best description over all adsorption temperatures and CO2 concentrations. Heterogeneity of the adsorbent surface was confirmed from Temkin adsorption isotherm model fit and isosteric heat of adsorption values. Spontaneous, feasible and exothermic nature was confirmed from negative values of ΔG° and ΔH°. Overall, very high surface area of carbon adsorbent makes this adsorbent a new promising carbon material for CO2 capture from power plant flue gas and for other relevant applications.
Keywords: Nanocasting; Adsorption kinetics; Adsorption equilibrium isotherm; Thermodynamics; KOH activation